Modular field robot deployment for inspection of dilapidated buildings. Issue 4 (30th April 2019) - Cordie, Troy P.; Bandyopadhyay, Tirthankar; Roberts, Jonathan; Dunbabin, Matthew; Greenop, Kelly; Dungavell, Ross; Steindl, Ryan
Abstract: Robotic inspection often relies on building custom platforms for each new deployment; this is a luxury that urban search and rescue (USAR) robots do not have when time is of critical importance. A significant factor for robots deployed in disaster areas is the varying size of voids and access ways in their path. These situations require platforms that can quickly reconfigure on location. With these challenges in mind, we present the NeWheel system: An in‐field reconfigurable robotic platform that allows mobility changes before, and during, deployment. The NeWheel platform also has the advantage of being small enough to be person‐deployable and to travel as checked luggage on a commercial flight. This field report presents the results and learnings from three field trips on Peel Island located off the coast of Brisbane, Australia. These field trips featured the deployment of the NeWheel system in multiple configurations to inspect and map inside historic dilapidated buildings. It demonstrates the potential of the NeWheel in buildings cluttered with debris and with unstable flooring whether they are historically important or in USAR contexts.